Laparoscopic Pancreaticoduodenectomy Versus Conventional Open Approach for Patients With Pancreatic Duct Adenocarcinoma: An Up-to-Date Systematic Review and Meta-Analysis - Feng, Qingbo; Liao, Wenwei; Xin, Zechang; Jin, Hongyu; Du, Jinpeng; Cai, Yunshi; Liao, Mingheng; Yuan, Kefei; Zeng, Yong (Frontiers in Oncology, 2021)
Background To compare perioperative and oncological outcomes of pancreatic duct adenocarcinoma (PDAC) after laparoscopic versus open pancreaticoduodenectomy (LPD vs. OPD), we performed a meta-analysis of currently available propensity score matching studies and large-scale retrospective cohorts to compare the safety and overall effect of LPD to OPD for patients with PDAC. Methods A meta-analysis was registered at PROSPERO and the registration number is CRD42021250395. PubMed, Web of Science, EMBASE, Cochrane Central Register of Controlled Trials, and ClinicalTrials.gov databases were searched based on a defined search strategy to identify eligible studies before March 2021. Data on operative times, blood loss, 30-day mortality, reoperation, length of hospital stay (LOS), overall morbidity, Clavien–Dindo ≥3 complications, postoperative pancreatic fistula (POPF), blood transfusion, delayed gastric emptying (DGE), postpancreatectomy hemorrhage (PPH), and oncologic outcomes (R0 resection, lymph node dissection, overall survival, and long-term survival) were subjected to meta-analysis. Results Overall, we identified 10 retrospective studies enrolling a total of 11,535 patients (1,514 and 10,021 patients underwent LPD and OPD, respectively). The present meta-analysis showed that there were no significant differences in overall survival time, 1-year survival, 2-year survival, 30-day mortality, Clavien-Dindo ≥3 complications, POPF, DGE, PPH, and lymph node dissection between the LPD and OPD groups. Nevertheless, compared with the OPD group, LPD resulted in significantly higher rate of R0 resection (OR: 1.22; 95% CI 1.06–1.40; p = 0.005), longer operative time (WMD: 60.01 min; 95% CI 23.23–96.79; p = 0.001), lower Clavien–Dindo grade ≥III rate (p = 0.02), less blood loss (WMD: −96.49 ml; 95% CI −165.14 to −27.83; p = 0.006), lower overall morbidity rate (OR: 0.65; 95% CI 0.50 to 0.85; p = 0.002), shorter LOS (MD = −2.73; 95% CI −4.44 to −1.03; p = 0.002), higher 4-year survival time (p = 0.04), 5-year survival time (p = 0.001), and earlier time to starting adjuvant chemotherapy after surgery (OR: −10.86; 95% CI −19.42 to −2.30; p = 0.01). Conclusions LPD is a safe and feasible alternative to OPD for patients with PDAC, and compared with OPD, LPD seemed to provide a similar OS. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/#recordDetails.